2019
DOI: 10.1021/acs.joc.9b00324
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Difluoromethylation of Aryl Chlorides and Bromides with TMSCF2H

Abstract: A palladium-catalyzed cross-coupling of aryl chlorides/bromides with TMSCF2H is described. Two different catalysts, Pd­(dba)2/BrettPhos and Pd­(P t Bu3)2, are demonstrated and provide a variety of difluoromethylated arenes in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…To evaluate the applicability of the synthesized gold complexes as difluoromethylating reagents, we set out to explore a Pd-catalyzed difluoromethylation of aryl iodides by means of a stoichiometric Au−Pd transmetalation 20 of the difluoromethyl moiety. Although this transformation has already been achieved with a single palladium 21 or copper 5d catalysts or with a bimetallic Ag−Pd system, 7a the results obtained in these studies will hopefully contribute to a better understanding of the unexploited Au−M bimetallic catalytic processes, since as demonstrated in previous reports in the literature, the transmetalation is a key step in the catalytic cycle. 22 4-Iodobiphenyl (17a) and (p-OMe-Ph) 3 PAu-CF 2 H (1b) were selected as model systems to study the desired transformation.…”
mentioning
confidence: 75%
“…To evaluate the applicability of the synthesized gold complexes as difluoromethylating reagents, we set out to explore a Pd-catalyzed difluoromethylation of aryl iodides by means of a stoichiometric Au−Pd transmetalation 20 of the difluoromethyl moiety. Although this transformation has already been achieved with a single palladium 21 or copper 5d catalysts or with a bimetallic Ag−Pd system, 7a the results obtained in these studies will hopefully contribute to a better understanding of the unexploited Au−M bimetallic catalytic processes, since as demonstrated in previous reports in the literature, the transmetalation is a key step in the catalytic cycle. 22 4-Iodobiphenyl (17a) and (p-OMe-Ph) 3 PAu-CF 2 H (1b) were selected as model systems to study the desired transformation.…”
mentioning
confidence: 75%
“…In 2019, Sanford and co-workers reported the Pd-catalysed difluoromethylation of aryl chlorides/bromides with TMSCF 2 H (Scheme 8E). 61 The authors identified optimal catalysts, either Pd(dba) 2 /BrettPhos Scheme 7 Copper-catalysed difluoromethylation of aryl iodides. or Pd(PtBu 3 ) 2 , and found that electron-neutral and electronrich substrates performed well under the optimised reaction conditions.…”
Section: C(sp 2 )-Cf 2 H Bond Formation: Cross-couplingmentioning
confidence: 99%
“…87B). 126,127,30 These reactions can be categorized as: cross-couplings of organohalides or pseudohalides with TMSCF2H, 146,147 structurally well-defined difluoromethylmetal complexes, [148][149][150][151][152] or C-H difluoromethylation with TMSCF2H 163,164 or difluoromethyl radical sources [165][166][167][168][169][170] (FIG. 8Ca-b7Bc and FIG.…”
Section: [H2] Difluoromethylationmentioning
confidence: 99%
“…We have made a modification.] Many recently developed carbon difluoromethylation methods have shown potential for the late-stage modification of pharmaceuticals and complex molecules, both through C-H difluoromethylation133,140,162,165,167,174,177,[213][214][215][216] and the substitution of prefunctionalized groups such as halogen,147,149,153 carboxyl,132,151 hydroxyl162 and amino groups145,150 with CF2H. Direct C-H radical difluoromethylation of heterocycles with difluoromethanesulfinate salts is arguably the most significant Formatted: Font color: Red Formatted: Font color: Red 25 / 62 achievement in this field; together with alkanesulfinate chemistry, this technique has found immediate application in drug discovery owing to its simplicity, the high tolerance towards functional groups and the predictability of site selectivity 217.…”
mentioning
confidence: 99%